Tax Policy Changes, Tax Revenue, Gross Domestic Product, and Budget Deficit: Evidence from Sri Lanka - Anojan, Vickneswaran; Thanuja, Vickneshwaran (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
The main objective is to investigate the relationship between Tax Policy Changes (TPCs), Tax Revenue (TR), and Gross Domestic Product (GDP) in Sri Lanka. Moreover, the relationship between TR, GDP, and Budget Deficit (BD) is investigated in this study. This study covers data for the period 2001-2021. Results show no significant relationship between tax policy changes and tax revenue in Sri Lanka. However, tax policy changes are significantly associated with GDP. Importantly, tax revenue is significantly associated with the budget deficit, while GDP also plays a significant role in shaping the budget deficit. This study concludes that no significant relationship between tax policy changes and tax revenue, but tax revenue and gross domestic production are significantly associated with the budget deficit. Therefore, stakeholders, especially policymakers ought to prioritize developing effective and efficient tax policies to positively influence the tax revenue, potentially reducing the budget deficit, and better managing the budget deficit in the future.